Development of Intrinsically Photoluminescent and Photostable Polylactones. (26th March 2014) - Xie, Zhiwei; Zhang, Yi; Liu, Li; Weng, Hong; Mason, Ralph P.; Tang, Liping; Nguyen, Kytai T.; Hsieh, Jer‐Tsong; Yang, Jian
<x xml:space="preserve">Abstract</x> A method of introducing intrinsically photo luminescent properties to biodegradable polymer is introduced, exemplified by the synthesis of intrinsically photoluminescent polylactones that enable non‐invasive monitoring and tracking of material degradation in vivo in realtime, as well as the formation of theranostic nanoparticles for cancer imaging and drug delivery. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>